A microhistological key for the identification of plant fragments in herbivore droppings from Mongolia’s steppe and semi-desert. - Bayarmaa Chuluunbat; Gantumur Khuderchuluun; Munkhtulga Dariganga; Nyambayar Batbayar; Badamdorj Bayartogtokh (Mongolian Journal of Biological Sciences)
Herbivores play a crucial role in maintaining the ecological balance of rangelands, making accurate dietary analysis essential for both wildlife conservation and livestock management. In Mongolia, where livestock husbandry is widespread, understanding the diets of both wildlife and livestock is vital for sustainable ecosystem management. Microhistology remains one of the most effective methods for herbivore diet analysis, yet the scarcity of comprehensive reference materials poses significant challenges. To address this, we developed an identification key based on the micro-anatomical characteristics of plant fragments found in herbivore feces from Mongolia’s steppe and semi-desert regions. This study examined 93 plant species, focusing on epidermal cell types, stomatal patterns, trichomes, and specialized cells. Key anatomical features, such as elongated, lobed, and angular epidermal cells, along with various stomatal configurations, were essential for plant identification, with anomocytic stomata being particularly prevalent. The diversity of trichomes, including ligulate and prickle types, provided additional clarity for distinguishing dicot species. Additionally, cork and dumbbell-shaped silica cells, especially in Cleistogenes, further aided in taxonomic classification. Our findings enhance the reliability of microhistological diet analysis, offering a tool to support wildlife conservation and sustainable grazing practices in the face of increasing grazing pressures and habitat degradation.